Separation of amine-insoluble species by flotation with nano and microbubbles. (April 2016) - Calgaroto, S.; Azevedo, A.; Rubio, J.
Graphical abstract: Highlights: The decyltrimethyl ether amine, collector used in the ore industry but toxic in water, precipitates at pH > 10.5. The removal of the amine precipitates was efficient by flotation with nanobubbles only. The nanobubbles aggregated the amine precipitates forming readily floating clusters. Residual amine, after flotation, was about 6 mg L −1, a very low and sustainable concentration in water. Abstract: Amines (alkylamines–ether amines) are employed on a large scale to separate iron ores by reverse flotation of the gangue particles (mostly quartz and silicates). Quartz gangue particles coated with amine collector are dumped in tailings dams as concentrated pulps. Then, the fraction of the amines that detach from the surfaces and the portion that is soluble in water, contaminate surface and ground-water supplies. This work presents a novel flotation technique to remove decyl-trimethyl-ether-amine (collector employed in Brazilian iron mines) from water. This amine forms precipitates at pH > 10.5 which are removed by flotation with microbubbles (MBs: 30–100 μm) and nanobubbles (NBs: 150–800 nm). Bubbles were generated simultaneously by depressurization of air-saturated water ( P sat of 66.1 psi during 25 min) forced through a flow constrictor (needle valve). The flotation by these bubbles is known as DAF-dissolved air flotation, one of the most efficient separation technologies in water and wastewater treatment. Herein, best results (80% amine removal) were obtained only after selective separation of the MBs from the NBs exploring the fact that while the NBs remain dispersed in water, the MBs rise leaving the system. The MBs, because of their buoyancy, rise too rapidly and do not collide and adhere appropriately at the amine colloids/water interface, even causing some precipitates breakage. It was found that the "isolated" NBs attach onto the amine precipitates; aggregate (flocculate) them and entrain inside the flocs before rising by flotation. Because of the low residual amine concentration in water (6 mg L −1 ), it is believed that this flotation technique have potential in this particular treatment of residual amine-bearing effluents.